PENYEBAB BERALIHNYA TEKNOLOGI DARI PEMILIK KEPADA PENERIMA - Bakti Trisnawati (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
Technology Transfer needs to be done, as long as it benefits the nation's economy. Technology transfer contracts are not only limited to the regulation of rights and obligations, but further implementation is still needed. Because the technology transfer contract has a relationship with the environment and society. As a result, it can affect the economic life of the country. In such conditions the need for government intervention in making technology transfer contracts. There is government interference, meaning there must be legal intervention. All of this should be explicitly reflected in the technology transfer contract agreement. Making agreements or contracts that are solely left to the operation of the principle of the principle of freedom of contract, will always be an arena of struggle for dominance between the parties to the agreement. Usually as a party that receives technology (in this case developing countries) is in a weak position, while the technology provider / owner is in a strong position. Thus the strong party will dominate the weak party, so that this situation often brings the result of a one-sided contract.